A Study of Selected Crimes Committed in Nigeria - Ayenigba Alfred Ayo; Ajao Olutunde Michael (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study conducts a detailed statistical analysis of criminal offenses across Nigeria's 36 states and the Federal Capital Territory (FCT), using data from the National Bureau of Statistics (NBS). Focusing on four primary crime categories, the research highlights significant regional disparities in crime frequency and nature. Lagos State is identified as the most affected area, with nearly 50,000 reported cases, attributed to its dense population and economic significance. The Federal Capital Territory and Cross River State also show high crime rates, though notably lower than Lagos. In contrast, states like Kebbi, Jigawa, and Zamfara report minimal criminal activity. Regionally, the South West zone records the highest crime frequencies, particularly in offenses against property and persons, while the North Central zone is predominantly affected by property crimes. Chi-Square analysis (χ² = 8171.757, p < 0.001) confirms a significant association between crime types and geographical zones. Correlation analysis reveals strong positive relationships between certain crime types, such as offenses against persons and property (r = 0.783). These findings underscore the complex and regionally varied nature of crime in Nigeria, highlighting the need for tailored, location-specific law enforcement and crime prevention strategies. The study provides crucial insights for policymakers and law enforcement agencies, emphasizing the importance of considering regional socio-economic and demographic factors in crime reduction efforts.